Application of MAPO (Movement and Assistance of Hospitalized Patients) method in hospitals and nursing homes: frequency of manual patient handling-part 2. Issue 9 (2nd September 2022) - Menoni, O.; Tasso, M.; Manno, R.; Battevi, N.
Abstract: This study examines the evolution of MAPO method for estimating the frequency of overloading tasks in healthcare workers during different shifts. The data presented were collected from 51 in-patient wards (25 hospitals and 26 nursing homes), and 917 workers: the frequency of MPH tasks is a complementary value to the MAPO exposure level, which is useful to implement a prevention plan targeted towards the reduction of overloading tasks. Based on the frequency of manual patient handling, it appears that the afternoon shift is at greatest risk, with tasks liable to cause overloading occurring within a frequency range of 70–85 per worker. The study analyzes different pieces of equipment and their relative percentages of use, concluding that, overall, they are underutilised (especially minor aids and height-adjustable beds). Practitioner summary: The organisational data collected in hospitals and nursing homes confirms the availability of patient handling aids and equipment, but also indicates that they are underutilised with respect to the frequency of overloading tasks.